Effect of Social Audit on Effective Operation of Public Expenditure - Ramesh Prasad Gautam, (Journal of Nepalese Management and Research, 2024)
Social Audits allow people to enforce accountability and transparency, allowing the ultimate users to scrutinize development initiatives. Data for the paper is collected from primary sources, such as questionnaires and surveys. The statistical sample of this study is collected from 10 different projects located at Chaukune Nagarpalika, Surkhet district. The study's main objective is to assess the effect of social audit on the effective operation of public expenditure in Chaukune Rural municipality of Surkhet district. In this survey, 185 employees are involved in the self-administered questionnaire with the help of the purposive-based convenience sampling technique. The data are checked using the statistical software SPSS 25 to perform descriptive analysis and regression. Five hypotheses are developed to analyze the effects of all the independent variables on the overall effective operation of public expenditure. The study finds that financial decision-making and communication significantly impact effective public expenditure operations in selected construction projects. Similarly, financial transparency, corporate governance, and awareness among beneficiaries have no significant role in the effective operation of public expenditure. Results also indicate that there is a relationship between social audit and the operation of public expenditure.